Al-Quran Sebagai Sumber Kisah: Mengasah Keterampilan Memproduksi Kisah Bagi Pendidik Anak Usia Dini - Hidayati, Laily (ACIECE, 2018)
One of the main contents of the holy Quran is the story or history of the past, which is explainedin the purpose of the revealed Quran as a guide and guidance for the life of the human being,then the Quran verses story are to be learned as a lesson so that human can easily carry out thetasks of creation throughout their life span. The human life span is calculated since he was borninto this world with the age of 0 years until the end of his life, which includes infancy, childhood,adolescence, adulthood, elderly, until the end of one's age. In that age range, DevelopmentalPsychologists have agreed that there is a period in a human's life span, which is considered themost crucial and most important period as a basis for the formation of human beings who willsail the ark of life throughout their lives. The period is known as the golden age or "golden age",namely the period between 0-5 years in the range of human development. In the widercommunity, this period is known as the early age. In this early age there is a "critical age" whichis the most appropriate period for a child to receive growth stimulation for all aspects of hisgrowth, which includes aspects of cognitive development, language, social emotional, artistic,motoric, and moral religious values. So this period is a general concern for the best stimulationto be passed in order to form a solid foundation that will be a strong pillar of human identity.The stimulation will not be carried out effectively without knowledge of the appropriate method.This paper wants to explore the use of storytelling methods and the practice of producingstories from the Quran which are one of the aspects of special skills for early childhoodeducators in carrying out effective learning in the nuances of Islam